Schopenhauer’s Philosophy Of Love In Flaubert’s Madam Bovary And Fitzgerald’s The Great Gatsby - Shamsi, Mahdi (2009)

(untitled)
This study examines the works of two writers F. Scott Fitzgerald’s The Great Gatsby and Flaubert’s Madam Bovary in relation to the concept of Schopenhauer’s philosophy of the ‚instinct of sex‛ as a subjective necessity and ‚love‛ as an objective point. The study determines whether the concepts of Schopenhauer, specifically on love, desire, and suffering, influence the life of the major characters in the two novels.This research is based on how Schopenhauer’s concept of ‚love as physical attraction‛ is portrayed in the characters of two novels. The study also attempts to find out what part the instinct of sex as a subjective point and the elements of desire, suffering and love as an objective point, plays in the lives of the characters. The research concludes that love among the characters is merely based on physical attraction, which leads them to have a strong desire which in turn, causes them to suffer.